Celebrating Cuba! Collaborating to Provide Global Access to the Cuban National Library's Catalog Records. Issue 3 (1st October 2017) - Van Kleeck, David
Abstract: This article outlines a highly collaborative effort among the Biblioteca Nacional de Cuba José Martí (BNJM), the University of Florida's George A. Smathers Libraries, and OCLC to open the Cuban national library's collections to researchers around the world. WorldCat now lists over 134, 000 catalog records with BNJM's holdings attached. Many of these records required the creation of original MARC records based on images from scanned catalog cards. An overview of the project is followed by a discussion of the cataloging-related processes involved, and a brief analysis of the ongoing work. This effort has opened previously unknown collections to researchers outside of Cuba, and will have a major impact on Cuba-related research well into the future.